Fire Risk Assessment of High-rise Buildings Based on Gray-FAHP Mathematical Model. (2018) - Li, Shi-yu; Tao, Gang; Zhang, Li-jing
Abstract: Fire risk assessment is the basic way to reduce and control the fire of high-rise buildings. In this essay the factors that affect the fire of high-rise buildings are analyzed to set up assessment index system of the fire rise for high-rise buildings whose main factors are fire safety hardware facilities, fire safety evacuation ability, building fire prevention capability and building fire safety management status. The gray risk degree method, AHP and the fuzzy evaluation method are used to establish the mathematical model. This model is applied to analyze and compare the fire risk of 5 high-rise buildings, such as Shaanxi Information Building, Zhongguancun Science and Technology Building and so on. The results show that the fire safety level of the high-rise buildings with function of office represented by the Shaanxi Information Building is "good", but the fire extinguishing system and the fire elevator equipment still need to be checked and maintained regularly, while the fire safety level of the high-rise buildings with the functions of shopping malls and residential buildings is "medium", which needs re-reasonable division of fire and smoke partition and improvement of the emergency response capability.